2017
DOI: 10.1016/j.nrl.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Beneficios de la musicoterapia en las alteraciones conductuales de la demencia. Revisión sistemática

Abstract: Music therapy is beneficial and improves behavior disorders, anxiety and agitation in subjects diagnosed with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 15 publications
1
10
0
13
Order By: Relevance
“…Our systematic review of studies on the effects of music therapy of patients living with dementia suggests significant improvements in verbal and language fluency, alleviation of BPSD including anxiety and depression and reduced levels of apathy. These findings are generally in line with previous reports on the potential benefits of music therapy in improving the behavioral symptoms in patients living with dementia [53,54]. However, our study suggests that music therapy failed to significantly improve the overall aspects of cognition (such as memory, orientation, and registration), agitation, daily functioning, and the quality of life of patients living with dementia.…”
Section: Discussionsupporting
confidence: 91%
“…Our systematic review of studies on the effects of music therapy of patients living with dementia suggests significant improvements in verbal and language fluency, alleviation of BPSD including anxiety and depression and reduced levels of apathy. These findings are generally in line with previous reports on the potential benefits of music therapy in improving the behavioral symptoms in patients living with dementia [53,54]. However, our study suggests that music therapy failed to significantly improve the overall aspects of cognition (such as memory, orientation, and registration), agitation, daily functioning, and the quality of life of patients living with dementia.…”
Section: Discussionsupporting
confidence: 91%
“…3 rationalised the oscillatory nature of FT¢ spectra as being deliberate. However, the added evidential dimension of FT¢ oscillatory behaviour being ratio-based may also rationalise a connectedness to music-based neurophysiological research, which for example has found: (i) a strong association between rhythm (perception skills) and language development in young children that is linked to the sharing of neural networks/cognitive resources between rhythm and grammatical structure learning [69]; (ii) that listening to classical music (by musically experienced participants) enhances the activity of genes responsible for brain function (in particular genes involved with dopamine secretion and transport, synaptic neurotransmission, learning and memory), with the synuclein-alpha gene (a known risk gene for Parkinson's disease) being one of the most enhanced [9]; (iii) benefits of music therapy for the treatment of dementia-based behavioural disorders [70]; and more generally (iv) multiple effects, both structural and functional, on the cerebral cortex in response to deliberate music exposure [6,7,9] (these examples represent only a small subset of a profusion of music-based neurophysiological research).…”
Section: The Sensitivity Of Ft¢ Towards Neuropathologymentioning
confidence: 99%
“…Finally, active aging takes place in the best possible (physical, psychological and social) conditions, it entails few -or none-losses of the psychosocial, physical and/or cognitive abilities, resulting in a better quality of life and life expectancy (5). Therefore, it implies and directly depends on certain environmental factors such as physical exercise (7), adequate nutrition (8), educational level (9), social and leisure activities (10), promotion of alternative, non-pharmacological therapies, among others (11).…”
Section: Introductionmentioning
confidence: 99%